Long-Term Outcome of Enterprise Stenting for Symptomatic ICAS in a High-Volume Stroke Center - Cui, Rongrong; Yan, Long; Kang, Kaijiang; Yang, Ming; Yu, Ying; Mo, Dapeng; Gao, Feng; Wang, Yongjun; Lou, Xin; Miao, Zhongrong; Ma, Ning (Frontiers in Neurology, 2021)
Background and Purpose: The Enterprise stent has been used for treating intracranial atherosclerotic stenosis (ICAS), but its long-term outcome remains unclear. The purpose of this study was to evaluate the long-term clinical efficacy of the Enterprise stent used for patients with symptomatic ICAS due to hypoperfusion. Method: Patients with symptomatic ICAS due to hypoperfusion treated with the Enterprise stents from a high-volume stroke center were evaluated. The successful recanalization was defined as the Modified Thrombolysis In Cerebral Infarction (mTICI) ≥ 2b. The stroke and neurological death that occurred within 72 h after the procedure as well as long-term clinical and imaging outcomes were analyzed. Results: Overall, 130 patients with 130 ICAS treated with the Enterprise stent were included in our study. The successful recanalization rate was 100%. The mean pre- and postprocedural stenosis was 82.9 ± 8.9% vs. 15.1 ± 8.4%. Periprocedural complications occurred in 5 (3.8%) patients within 72 h after the procedure. Clinical follow-up data were available in 125 (96.2%) patients (median, 24 months) and any stroke or neurological death was encountered in 6 (4.8%) patients. Angiographic follow-up data was obtained from 118 (90.8%) patients (median, 13.5 months). In addition, 1-year in-stent restenosis (>70%) was found in 17 (14.4%) patients, and among them, 4 (23.5%) patients were symptomatic. Conclusion: Deployment of Enterprise stent is safe for ICAS. The short-term and long-term outcomes were acceptable, but the efficacy of the Enterprise stent needs to be further evaluated in future studies.